2018
DOI: 10.1002/jssc.201800960
|View full text |Cite
|
Sign up to set email alerts
|

Study on the metabolites of betulinic acid in vivo and in vitro by ultra high performance liquid chromatography with time‐of‐flight mass spectrometry

Abstract: Betulinic acid is a triterpenoid organic acid with remarkable antitumor properties and is naturally present in many fruits, condiments and traditional Chinese medicines. Currently, a strategy was developed for the identification of metabolites following the in vivo and in vitro biotransformation of Betulinic acid with rat intestinal bacteria utilizing ultra high performance liquid chromatography with time‐of‐flight mass spectrometry with polymeric solid‐phase extraction. As a result, 46 metabolites were struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The screening mass spectra of analyzed samples indicated the presence of the precursor ion identified as [M-H] − at m / z 469.37 ( M5 ),which has a Mw 14 Da more than BA, and was assigned according to the mass calculations to the methylated metabolite of BA, which is consistent with previous findings that reported methylated metabolites for echinocystic acid, a triterpene [ 39 ], as well as for BA [ 22 , 23 ]. Although methylation is a minor conjugation reaction for xenobiotic transformation, being more common for endogenous neurotransmitters, it still remains a metabolic pathway for a large number of medicinal drugs and phytocompounds [ 38 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The screening mass spectra of analyzed samples indicated the presence of the precursor ion identified as [M-H] − at m / z 469.37 ( M5 ),which has a Mw 14 Da more than BA, and was assigned according to the mass calculations to the methylated metabolite of BA, which is consistent with previous findings that reported methylated metabolites for echinocystic acid, a triterpene [ 39 ], as well as for BA [ 22 , 23 ]. Although methylation is a minor conjugation reaction for xenobiotic transformation, being more common for endogenous neurotransmitters, it still remains a metabolic pathway for a large number of medicinal drugs and phytocompounds [ 38 ].…”
Section: Resultssupporting
confidence: 87%
“…The available data regarding the in vivo metabolism of BA are even more limited, hence only a couple of studies have been published. Recently, Zhang et al [ 22 ] reported on some phase I metabolites identified in the feces of Sprague-Dawley rats after oral administration of BA-carboxyl methyl cellulose solution. Another study conducted by Li et al [ 23 ] reported on other phase I and phase II metabolites of BA mainly identified in the feces of Sprague-Dawley rats after oral administration of BA, spinosin, isovitexin and jujuboside together with Ziziphi Spinosae semen extract.…”
Section: Introductionmentioning
confidence: 99%
“…The relative quantitative estimation of metabolites was carried out on the basis of the peak areas of XICs. The area normalization method was utilized to estimate relative quantification of metabolites . Then, the peak area ratio ( W %) of each metabolite in a specific matrix was expressed as follows: W % = the peak area of each metabolite/the peak area of parent drug and all metabolites × 100% in the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The area normalization method was utilized to estimate relative quantification of metabolites. 33 Then, the peak area ratio (W%) of each metabolite in a specific matrix was expressed as follows: W% = the peak area of each metabolite/ the peak area of parent drug and all metabolites × 100% in the matrix. The peak areas of acacetin and metabolites that were detected in blood, bile, urine, feces, and microsomes were calculated and are listed in Supplementary Table 1.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…In this study, it was the first time to develop a rapid and reliable method to analyze and identify the metabolites of 5-O-methylvisammioside in vivo and in vitro by combining UHPLC-Q-TOF-MS/MS with multiple data processing technologies. In addition, area normalization method was applied to evaluate the relative contents of metabolites in each biological sample for exploring the major metabolic pathway [17]. As a result, based on accurate masses, chromatographic behaviors and MS/MS fragment ions, 26 metabolites in vivo and seven metabolites in vitro were detected, and the metabolic pathways were summarized and compared.…”
mentioning
confidence: 99%